2019
DOI: 10.1093/eurheartj/ehz008
|View full text |Cite
|
Sign up to set email alerts
|

Stage-dependent differential effects of interleukin-1 isoforms on experimental atherosclerosis

Abstract: Aims Targeting interleukin-1 (IL-1) represents a novel therapeutic approach to atherosclerosis. CANTOS demonstrated the benefits of IL-1β neutralization in patients post-myocardial infarction with residual inflammatory risk. Yet, some mouse data have shown a prominent role of IL-1α rather than IL-1β in atherosclerosis, or even a deleterious effect of IL-1 on outward arterial remodelling in atherosclerosis-susceptible mice. To shed light on these disparate results, this study investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 38 publications
0
70
0
Order By: Relevance
“…On the other side, Jiang et al [9] recently found that inhibiting the NLRP3 inflammasome using MCC950 reduced LPS- or ATP-induced IL-1α release in plaque-derived tissue. The exact role of IL-1α in atherogenesis is still not clear, however, it seems to be of importance for metabolic-induced inflammation, as it was recently shown to promote vascular remodelling [35] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, Jiang et al [9] recently found that inhibiting the NLRP3 inflammasome using MCC950 reduced LPS- or ATP-induced IL-1α release in plaque-derived tissue. The exact role of IL-1α in atherogenesis is still not clear, however, it seems to be of importance for metabolic-induced inflammation, as it was recently shown to promote vascular remodelling [35] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these modified LDLs can cause oxidative stress, inflammation, NLRP3 inflammasome activation, and immune response, thus amplifying the vicious cycle of atherogenic cellular events (Steinberg and Witztum, 2010;Wang et al, 2017h). In addition to modified LDL, interleukin 1 (IL-1) (IL-1a and IL-1b) also drives vascular inflammation, with IL-1a mainly being involved in arterial remodeling during the early phase of atherosclerosis, whereas IL-1b drives inflammation and atheroprogression to advanced state of atherosclerosis (Vromman et al, 2019). The recent CANTOS clinical trial has shown that anti-inflammatory effect with canakinumab (a monoclonal antibody targeting IL-1b) significantly reduces the rate of recurrent cardiovascular events in patients with atherosclerotic diseases without reducing the lipid levels (Ridker et al, 2017).…”
Section: Atherosclerosis: An Introductionmentioning
confidence: 99%
“…Osteoblast is responsible for bone formation, [24][25][26] and MC3T3-E1 cells are precursors of osteoblasts. Since IL-10 regulates arthritis development, 12,13 we speculated that IL-10 is involved in the osteogenic capacity of MC3T3-E1 cells.…”
Section: Il-10 Targets Both Innate and Adaptive Immune Responses And Ex-mentioning
confidence: 99%